THE NON-ADIABATIC NATURE OF MANTLE CONVECTION AS REVEALED BY PASSIVE TRACERS - Steinbach V.; Yuen D.A. (My University, 1995)
We have investigated the state of adiabaticity in mantle flows by using a Lagrangian tracer technique to map out the thermal state of parcels in both downwelling and upwelling flows in mantle flush events. The model, based on a core-cooling boundary condition, has two major phase transitions and a temperature-dependent viscosity. The temperature histories of the first tracers that enter into the lower mantle during a flushing event reveal a superadiabatic increase of up to 700 K, due to conduction and viscous dissipation. The lateral temperature anomalies in the deep lower mantle, monitored by the tracers, can exceed 1000 K. The cold sinking anomalies follow a superadiabatic path and are heated up according to the time-history of the flush event. The time-history of the rising parcels is strongly influenced non-adiabatically by the two phase transitions in the upper mantle, with only a small segment in the upper mantle below the surface, where the parcels are found to be invariably slightly superadiabatic. Following a major flush event, the horizontally averaged temperature profiles display strong subadiabaticity in the deep mantle and superadiabaticity in the transition zone. During this time the mean temperature profiles do not follow an adiabat anywhere. The concept of adiabaticity may have limited applications in strongly time-dependent mantle convection with phase transitions, where major overturns take place from time to time.